Pembinaan kepada Majelis Jemaat di Gereja Kristen Sulawesi Tengah (GKST) Anugerah Lena mengenai Panggilan Pelayanan - Tiladuru, Vena Melinda; Sihombing, Aeron Frior; Tampubolon, Yohanes Hasiholan; Prianto, Robi (Edumedia Solution, 2023)
The calling of service is an important concept in the context of church life. Within the church, each member is given a calling to serve according to the gifts bestowed upon them by God. It is crucial for the church to understand, strengthen, and facilitate the understanding of this calling for every individual within the congregation. The GKST Anugerah Lena congregation, as part of the Christian church community, is committed to encouraging and nurturing its members in understanding and developing their calling to service. In this regard, the community engagement team's journal activities (PKM) focus on the development of the calling to service within the GKST Anugerah Lena congregation. These PKM activities serve as a means to strengthen and solidify the calling to service for the members of the Majelis in GKST Anugerah Lena. This can help individuals within the congregation to have a clearer understanding of their personal calling within the church context and encourage them to live in accordance with that calling.